Ethical approach to digital skills. Sense and use in virtual educational spaces - Juan GARCÍA-GUTIÉRREZ (Ediciones Universidad de Salamanca, 2013)
In the context of technology and cyberspace, should we do everything we can do? The answer given to this question is not ethical, is political: safety. The safety and security are overshadowing the ethical question about the meaning of technology. Cyberspace imposes a "new logic" and new forms of "ownership". When it comes to the Internet in relation to children not always adopt logic of accountability to the cyberspace, Internet showing a space not only ethical and technical. We talk about safe Internet, Internet healthy, and Internet Fit for Children... why not talk over Internet ethics? With this work we approach digital skills as those skills that help us to position ourselves and guide us in cyberspace. Something that is not possible without also ethical skills. So, in this article we will try to build and propose a model for analyzing the virtual learning spaces (and cyberspace in general) based on the categories of "use" and "sense" as different levels of ownership that indicate the types of competences needed to access cyberspace.